Land Reforms in Post-Socialist Mountain Regions and their Impact on Land Use Management: a Case Study from the Caucasus - Alexey Gunya (Revue de Géographie Alpine)
The land reforms of the 1990s in the former Soviet republics led to the elimination of the state’s monopoly on the ownership of land, a revival in local communities and a rise in business activity. The consequences of these reforms include the almost total disappearance of collective farms and the emergence of the private ownership of land. In the 1990s, the state delegated political power, including the disposability of land, to local authorities. However, these changes in political power varied significantly from region to region. This article aims to explain the various institutional environments that have developed at the local level in reaction to land reforms. Our investigation of 18 key villages in the North Caucasus republics of Karachay-Cherkessia, Kabardino-Balkaria, North Ossetia, Ingushetia, Chechnya and Dagestan show that land reforms have galvanised multiple actors representing the state, as well as collectives, individuals and various formal and informal institutions that regulate relations between these actors. Along with the political factors – such as the level of centralisation and economic liberalisation – that have led to differences in the pace of land reforms, local natural and cultural conditions and communities play an important role. The latter are characterised either by conservatism or by readiness for reforms. Regarding the key villages, five different types were identified: 1) villages where most of the land has been redistributed among private owners (Karachay-Cherkessia); 2) villages that have preserved collective use (some settlements in the North Caucasus with mainly Russian population); 3) villages where access to land is regulated by the state (Chechnya); 4) villages where access to land is regulated by municipal bureaucracy at the district level (many other regions in the North Caucasus); and 5) villages where the right of access to land is in dispute between the government and the business and local communities (e.g. villages in the tourist areas of the North Caucasus).